Seismic Hazard Estimation for Sumatra and Kalimantan Region Using Event-Based Probabilistic Seismic Hazard Analysis (EB-PSHA) - Khalqillah, Aulia; Umar, Muksin; V. H. Simanjuntak, Andrean; Jihad, Abdi; H. Banyunegoro, Vrieslend (UIR PRESS, 2025)
Indonesia is located in a tectonically active region influenced by the interactions of several tectonic plates. This tectonics setting give rise to numerous active faults and subduction zones, making Indonesia highly susceptible to earthquakes. To mitigate earthquake risk, seismic hazard assessments are essential and contribute directly to the development of earthquake-resistant building codes or premium assets estimation for assets insurance. This study aims to assess seismic hazard analysis in Sumatra and Kalimantan using the Event-Based Probabilistic Seismic Hazard Analysis (EB-PSHA) method for a 250-year return period (0.4% annual exceedance probability in one year) for Peak Ground Acceleration (PGA) and Spectral Acceleration (SA) at 0.3 s and 0.6 s. Three seismic source models, Active Shallow Crusts, Subduction Interfaces, and Background Sources, are used in this analysis. A combined earthquake catalog from several agencies is used to estimate the magnitude of completeness ( ), a-value, and b-value based on the mainshock earthquake only. This analysis utilize Ground Motion Prediction Equations (GMPEs) randomly sampled to estimate the potential intensities. These findings reveal significant regional variations in seismicity, with the southern Sumatra showing high seismicity rate and the northern part indicating potential stress accumulation. Particularly in Bengkulu Province, due to the relative high seismicity rate based on the seismicity statistical parameters of a-value and b-value. It also suggests the influence of multiple megathrusts and active faults. In contrast, Kalimantan shows lower hazard overall, though East Kalimantan records localized high intensities due to the Meratus and Mangkahilat faults. Although Kalimantan’s seismicity is low, historical events demonstrate that distant earthquakes can still cause substantial impacts. The model has been validated by using six historical events and it is in good agreement more than 75% of correlation. The results offer valuable input for seismic risk analysis on the potential building loss estimation through Event Loss Table (ELT).